Trimethylamine methanesulfonate second-order nonlinear optical crystal material as well as preparation and application thereof
By introducing heterotetrahedral [SO3CH3]-groups into non-π-conjugated structural motifs, the second-order nonlinear optical crystal material of trimethylamine methylsulfonate was synthesized, and the problems of low polarization anisotropy and hyperpolarization of existing materials were solved, moderate frequency multiplication response and short ultraviolet absorption cut-off edges were achieved, and broad application prospects were achieved.
Patent Information
- Application Number
- CN202411989322.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-31
AI Technical Summary
Existing non-π-conjugated structural motifs such as [PO4]3- and [SO4]2-polarization anisotropy and hyperpolarization rates are low in deep ultraviolet light sources applications, limiting the practical application of nonlinear optical crystal materials.
By introducing heterotetrahedral [SO3CH3]-groups, the second-order nonlinear optical crystal material [(CH3)3NH]+[SO3CH3]- is synthesized to enhance its nonlinear optical properties.
The material exhibits moderate frequency multiplication response and short UV absorption cut-off edges, and is able to output strong 532nm green light under 1064nm laser irradiation, achieve phase matching, and have high transmittance and high thermal decomposition temperature.
Smart Images

Figure CN119753849A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nonlinear optical crystal materials, and relates to a trimethylammonium methanesulfonate second-order nonlinear optical crystal material and a preparation method and application thereof. Background Art
[0002] Coherent deep ultraviolet (DUV, λ<200nm) light sources are widely used in laser frequency conversion, laser ranging, laser communication, medical treatment, and national defense and military fields. The most effective way to generate DUV coherent light is to use the second harmonic generation (SHG) effect of nonlinear optical (NLO) crystal materials. [PO4] 3- and [SO4] 2- Non-π-conjugated structural units such as [PO4] have attracted widespread attention due to their large energy gap. However, the polarizability anisotropy and hyperpolarizability of these structural units are low, which limits the practical application of crystalline materials. 3- and [SO4] 2- Introducing heteroatoms or organic groups into non-π conjugated structural units to form heterotetrahedrons is an effective strategy to enhance structural anisotropy. According to the statistics of the inorganic crystal structure database, among the sulfur-containing heterotetrahedral-based crystals, crystals with non-centrosymmetric structures only account for 26% (non-centrosymmetric structures are a prerequisite for the material to have second harmonic generation). Therefore, the development of new sulfur-containing heterotetrahedral-based DUV NLO crystal materials is a research hotspot and difficulty in the field of optoelectronic technology. Summary of the invention
[0003] The purpose of the present invention is to provide a second-order nonlinear optical crystal material of trimethylammonium methanesulfonate and its preparation and application, and the heterogeneous tetrahedron [SO3CH3] in the provided material - The group enhances the nonlinear optical properties of methanesulfonate, making it exhibit a moderate double-frequency response (0.5×KH2PO4(KDP)) and a short ultraviolet absorption cutoff edge (λ<200nm).
[0004] The purpose of the present invention can be achieved by the following technical solutions:
[0005] In one aspect, the present invention provides a second-order nonlinear optical crystal material of trimethylammonium methanesulfonate, whose chemical formula is [(CH3)3NH] + [SO3CH3] - , molecular weight is 154.21, belongs to the orthorhombic system, and the space group is Pca21 (No.29). The unit cell parameters are α=γ=β=90°,Z=4,the unit cell volume is
[0006] Furthermore, the unit cell parameters of the crystal material are α=β=γ=90°, Z=4. Most preferably, the unit cell parameters are α=β=γ=90°, Z=4.
[0007] Inorganic compound crystals of the present invention [(CH3)3NH] + [SO3CH3] - The crystal structure of Figure 1 As shown. Each [SO3CH3] - The tetrahedron is formed by a central S atom coordinated by three O atoms and a CH3 group. [(CH3)3NH] + and [SO3CH3] - The tetrahedra are connected to each other through NH···O hydrogen bonds to form a three-dimensional structure.
[0008] On the other hand, the present invention provides a method for preparing a second-order nonlinear optical crystal material of trimethylammonium methanesulfonate, comprising mixing a N source, a S source and ethanol, and continuously stirring until a clear and transparent solution is obtained, then concentrating the clear and transparent solution by rotary evaporation, adding ethanol, and cooling and crystallizing under a low temperature environment to finally obtain colorless and transparent flaky crystals, which are the target product.
[0009] Furthermore, the added amounts of the N source and the S source satisfy the following: the molar ratio of the N element to the S element is (1-10):(1-10), preferably (1-5):(1-5).
[0010] Further, the N source is trimethylamine hydrochloride or trimethylamine aqueous solution. Preferably, the N source is trimethylamine hydrochloride.
[0011] Further, the S source is sodium methanesulfonate or methanesulfonic acid. Preferably, the S source is silver methanesulfonate.
[0012] Furthermore, the ratio of the added amount of the N source to the ethanol was 1 mmol:3 mL.
[0013] Furthermore, the temperature of the rotary evaporation concentration is 35-45°C.
[0014] Furthermore, the temperature of the cooling crystallization is 0-4°C and the time is not less than 1 week.
[0015] In a third aspect, the present invention provides an application of a second-order nonlinear optical crystal material of trimethylammonium methanesulfonate in a laser frequency converter, a photoelectric rectifier, an optical parametric oscillator, an optical parametric amplifier and a frequency doubling generator.
[0016] Furthermore, when the trimethylammonium methanesulfonate second-order nonlinear optical crystal material is used in a laser frequency converter, the crystal can output 532nm green light under 1064nm laser irradiation. Specifically, under 1064nm laser irradiation, a strong 532nm green laser is output, and its powder frequency-doubled intensity is about 0.5 times that of KDP crystal, and phase matching can be achieved.
[0017] The present invention utilizes the strategy of element substitution to form heterocoordinate tetrahedron [SO3CH3] - As an optical functional structural unit, the nonlinear optical crystal material [(CH3)3NH] was successfully synthesized + [SO3CH3] - , which exhibits a moderate frequency-doubling effect (0.5×KDP) and a short UV absorption cutoff edge (λ<200nm).
[0018] Compared with the prior art, the present invention has the following advantages:
[0019] (1) This application provides a new second-order nonlinear optical crystal [(CH3)3NH] + [SO3CH3] - , the crystal material is about 0.5 times the frequency doubling intensity of KDP crystal under 1064nm laser irradiation, and can achieve phase matching. In addition, the crystal material has a high transmittance in the 200-800nm spectral range, and the ultraviolet absorption cut-off wavelength is less than 200nm. The thermal decomposition temperature is 220℃. Therefore, the crystal material has broad application prospects in the field of second-order nonlinear optics.
[0020] (2) The present application also provides the nonlinear optical crystal [(CH3)3NH] + [SO3CH3] - The preparation method comprises the following steps: by rotary evaporation concentration, cooling and crystallization, finally growing colorless flaky crystals [(CH3)3NH] + [SO3CH3] - The method is convenient and has mild reaction conditions. It can efficiently prepare single crystals with high optical quality and high purity, which is conducive to large-scale industrial production.
[0021] (3) The trimethylammonium methanesulfonate crystal material of the present invention can be applied to a laser frequency converter, which can convert a laser beam into a double frequency harmonic output. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 is [(CH3)3NH] + [SO3CH3] - Schematic diagram of the crystal structure;
[0023] Figure 2is a comparison of X-ray diffraction patterns; (a) is an X-ray diffraction pattern obtained by analyzing and simulating the single crystal X-ray diffraction data of sample 1#; (b) is a pattern obtained by X-ray diffraction testing after sample 1# is ground into powder;
[0024] Figure 3 is the UV-Vis-NIR absorption spectrum of sample 1-1#;
[0025] Figure 4 is the infrared spectrum of sample 1-1#;
[0026] Figure 5 This is the thermogravimetric analysis spectrum of sample 1-1#;
[0027] Figure 6 It is the second harmonic signal diagram of sample 1-1# and standard KDP sample with sample size ranging from 200 to 280 μm;
[0028] Figure 7 This is the second harmonic phase matching diagram of sample 1-1# at a wavelength of 1064nm. DETAILED DESCRIPTION
[0029] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0030] In the following examples, unless otherwise specified, raw materials or processing techniques are conventional commercially available raw materials or conventional processing techniques in the art.
[0031] Example 1
[0032] Preparation of samples 1# to 8#
[0033] Mix the N source, S source and ethanol in a certain proportion to form a raw material, and stir continuously until a clear and transparent solution is obtained. After the clear and transparent solution is concentrated by rotary evaporation, a small amount of ethanol (concentration is 98%) is added, and cooled and crystallized at a low temperature environment of about 2°C to finally obtain colorless and transparent flakes [(CH3)3NH] + [SO3CH3] - Crystal.
[0034] The relationship between the type and ratio of raw materials in the initial mixture, rotary evaporation temperature, cooling time and sample number is shown in Table 1.
[0035] Table 1 Correspondence between samples, raw materials and synthesis conditions
[0036]
[0037] Crystal structure analysis of samples 1# to 8#
[0038] Single crystal X-ray diffraction and powder X-ray diffraction methods were used to perform structural analysis and phase analysis on samples 1#~8#, respectively.
[0039] The single crystal X-ray diffraction test was carried out on a D8 VENTURE CMOS X-ray single crystal diffractometer from Bruker, Germany. The data collection temperature was 298.15K, and the diffraction light source was graphite monochromatized Mo-Kα rays. The scanning mode was ω; the data were processed for absorption correction using the Multi-Scan method. The structure analysis was completed using the Olex2 program package; the positions of heavy atoms were determined using the direct method, and the coordinates of the remaining atoms were obtained using the difference Fourier synthesis method; the F-based 2 The full-matrix least-squares method was used to refine the coordinates of all atoms and the anisotropic thermal parameters.
[0040] Single crystal X-ray diffraction results show that samples 1# to 8# have the same chemical formula and crystal structure, and the chemical formula is [(CH3)3NH] + [SO3CH3] - , molecular weight is 154.21, belongs to the orthorhombic system, and the space group is Pca21 (No.29). The unit cell parameters are α=γ=β=90°,Z=4,the unit cell volume is
[0041] Take sample 1-1# as a typical representative, its crystal structure data is α=β=γ=90°, Z=4. [(CH3)3NH] + [SO3CH3] - Crystal structure Figure 1 shown.
[0042] The powder X-ray diffraction test was carried out on a Bruker D8 X-ray powder diffractometer from Bruker, Germany. The test conditions were a fixed target monochromatic light source Cu Kα, a wavelength of The voltage and current are 40 kV / 20 A, the slits DivSlit / RecSlit / SctSlit are 2.00 deg / 0.3 mm / 2.00 deg respectively, the scanning range is 10-70°, and the scanning step is 0.02°.
[0043] The powder X-ray diffraction test results show that in the XRD spectra of samples 1# to 8#, the peak positions of each sample are basically the same, but the peak intensities are slightly different.
[0044] Take sample 1# as a typical example. Figure 2As shown, according to the crystal structure analyzed by single crystal X-ray diffraction, the peak positions of the fitted X-ray diffraction pattern are consistent with the pattern obtained by X-ray diffraction test after sample 1# is ground into powder, which indicates that the obtained sample has a high purity.
[0045] UV-Vis-NIR absorption spectroscopy test
[0046] The diffuse reflectance absorption spectrum test of sample 1-1# was conducted on a Carry 5000 UV-visible-near infrared spectrophotometer from Agilent Technologies, USA. Figure 3 As shown, the compound has no obvious absorption in the range of 200nm to 800nm, and the optical band gap is less than 6.20eV. The wide optical band gap is conducive to the fundamental frequency light to pass through the crystal to generate second harmonic ultraviolet light. The material can be used in ultraviolet band laser frequency conversion, laser lithography and other fields.
[0047] Infrared spectrum test
[0048] The infrared spectrum test of sample 1# was conducted on a Nicolet iS10 Fourier infrared spectrometer from Thermo Fisher Scientific Inc., USA. The results are as follows Figure 4 As shown, 769cm in the infrared spectrum -1 、1024cm -1 The characteristic absorption peaks of [SO3CH3] - The presence of groups.
[0049] Thermogravimetric testing
[0050] The thermogravimetric test of sample 1# was conducted on a Netzsch STA 409PC thermogravimetric analyzer manufactured by Netzsch Equipment Manufacturing Co., Ltd., Germany. The results are shown in the figure below. Figure 5 As shown, the decomposition temperature of this compound is 220°C.
[0051] Frequency doubling test experiment and results
[0052] The frequency doubling test experiment of sample 1# is as follows: a laser with a wavelength of 1064nm generated by a Q-switched Nd:YAG solid laser is used as the fundamental frequency light to irradiate the tested crystal powder, a spectrometer is used to detect the generated second harmonic, and an oscilloscope is used to display the harmonic intensity. The crystal sample and the standard sample KDP crystal are ground separately, and crystals of different particle sizes are sieved out with a standard sieve, with the particle size ranges of 26-50, 50-105, 105-150, 150-200, and 200-280μm. Observe the change trend of the frequency doubling signal with the particle size to determine whether it can achieve phase matching. Under the same test conditions, the second harmonic intensities generated by the sample and the reference crystal KDP under 1064nm wavelength laser irradiation are compared to obtain the relative size of the sample frequency doubling effect.
[0053] The test results show that the compound [(CH3)3NH] + [SO3CH3] - When the crystal is irradiated with 1064nm wavelength laser, the frequency doubled signal intensity is 0.5 times that of KDP crystal (such as Figure 6 ).like Figure 7 As shown, the crystal material can achieve phase matching at a laser wavelength of 1064nm.
[0054] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A trimethylammonium methanesulfonate second-order nonlinear optical crystal material, characterized in that: Its chemical formula is [(CH3)3NH] + [SO3CH3] - , molecular weights are 154.21, belong to the orthorhombic system, space group is Pca21 (No.29), unit cell parameters are α=γ=β=90°,Z=4,the unit cell volume is 2. The trimethylammonium methanesulfonate second-order nonlinear optical crystal material according to claim 1, characterized in that: The unit cell parameters of the crystal material are α=β=γ=90°, Z=4.
3. The method for preparing a trimethylammonium methanesulfonate second-order nonlinear optical crystal material according to claim 1 or 2, characterized in that: The N source, S source and ethanol are mixed and stirred continuously until a clear and transparent solution is obtained. The clear and transparent solution is then concentrated by rotary evaporation, and ethanol is added. The solution is cooled and crystallized at a low temperature to finally obtain colorless and transparent flaky crystals, which are the target product.
4. The method for preparing a trimethylammonium methanesulfonate second-order nonlinear optical crystal material according to claim 3, characterized in that: The added amounts of the N source and the S source satisfy the following requirement: the molar ratio of the N element to the S element is (1-10):(1-10).
5. The method for preparing a trimethylammonium methanesulfonate second-order nonlinear optical crystal material according to claim 3, characterized in that: The N source is trimethylamine hydrochloride or trimethylamine aqueous solution.
6. The method for preparing a trimethylammonium methanesulfonate second-order nonlinear optical crystal material according to claim 3, characterized in that: The sulfur source is sodium methanesulfonate or methanesulfonic acid.
7. The method for preparing a trimethylammonium methanesulfonate second-order nonlinear optical crystal material according to claim 3, characterized in that: The ratio of the added amount of N source to ethanol was 1mmol:3mL.
8. The method for preparing a trimethylammonium methanesulfonate second-order nonlinear optical crystal material according to claim 3, characterized in that: The temperature of rotary evaporation concentration is 35-45°C; the temperature of cooling crystallization is 0-4°C, and the time is not less than 1 week.
9. Application of the trimethylammonium methanesulfonate second-order nonlinear optical crystal material as claimed in claim 1 or 2 in laser frequency converters, photoelectric rectifiers, optical parametric oscillators, optical parametric amplifiers and frequency doubling generators.
10. Use of the trimethylammonium methanesulfonate second-order nonlinear optical crystal material according to claim 9, It is characterized in that When the second-order nonlinear optical crystal material of trimethylammonium methanesulfonate is used in laser frequency converter, It can generate 532nm green light output under the irradiation of 1064nm laser.
Citation Information
Patent Citations
Nonlinear optical crystal barium methanesulfonate as well as preparation method and application thereof
CN116446051A
Mercury-based nitrate second-order nonlinear optical crystal material and preparation and application thereof
CN116949575A
Rare earth formate second-order nonlinear optical crystalline material and preparation and application thereof
CN118257002A
Cited By
Lithium 2-hydroxyethanesulfonate second-order nonlinear optical crystal and preparation and application thereof
CN121496572A
Amino methanesulfonic acid second-order nonlinear optical crystal as well as preparation and application thereof
CN121700524A